2017
DOI: 10.3745/jips.02.0063
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Secure Semi-fragile Watermarking Based on LBP and Arnold Transform

Abstract: In this paper, we analyze a recently proposed semi-fragile watermarking scheme based on local binary pattern (LBP) operators, and note that it has a fundamental flaw in the design. In this work, a binary watermark is embedded into image blocks by modifying the neighborhood pixels according to the LBP pattern. However, different image blocks might have the same LBP pattern, which can lead to false detection in watermark extraction process. In other words, one can modify the host image intentionally without affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Zhang et al [35] described analysis from the existing semi-fragile watermarking schemes based on local binary pattern (LBP) operators and concluded that there is a fundamental flaw in the design. In this work, a binary watermark is embedded into image blocks by modifying the neighborhood pixels according to the LBP pattern.…”
mentioning
confidence: 99%
“…Zhang et al [35] described analysis from the existing semi-fragile watermarking schemes based on local binary pattern (LBP) operators and concluded that there is a fundamental flaw in the design. In this work, a binary watermark is embedded into image blocks by modifying the neighborhood pixels according to the LBP pattern.…”
mentioning
confidence: 99%